PENGEMBANGAN ASPEK KEAGAMAAN ANAK USIA DINI - Rahmat Hidayat; Siti Khomsiyati (AZZAHRA, 2020)
Religious and moral values ​​in early childhood are very important to be developed so that students have a good understanding of religious values, so that in living life, children understand better the value of religious teachings and when students enter the next level, already have good knowledge and experience. The purpose of this research is to find out what innovations are needed in the development of early childhood religious values. This research was studied using descriptive methods and library research approaches as a place or source of reference. The results of the study indicate that the forms of early childhood diversity include Unreflective, Egocentric, Anthromorphic, Verbalist and Ritualist, and Imitative. Innovations made in developing AUD religious values ​​are through experiential learning, active learning and process learning. The principles of innovation for the development of AUD religious values ​​are the principle of developmentally appropriate practice (DAP), the principle of enjoyable. One of the learning models that can be used in developing the religious value of early childhood is the quantum learning model. Meanwhile, the methods for developing children's religious values ​​are play, travel, storytelling, singing and demonstration methods.